Konseling Individu dengan Teknik Rational Emotive Behaviour Therapy (REBT) dalam Meningkatkan Kepercayaan Diri (Studi Kasus Klien “A”) - Wahyu Muhamad Noufal; Abdur Razzaq; Zhila Jannati (Scidacplus, 2023)
The purpose of this research is to determine the description of lack of self-confidence, to determine the process of implementing individual counseling using the Rational Emotive Behavior Therapy technique, to determine the obstacles in individual counseling using the Rational Emotive Behavior Therapy technique. This research uses a qualitative research approach, and the research method used in this research is the case study method. Data collection tools in this research are observation, interviews and documentation. The data analysis techniques in this research are data reduction, data presentation, and conclusions or verification. The subject of this research is client